Outcomes and Barriers to Uptake of Cataract Surgery in Rural Northern China: The Heilongjiang Eye Study. (June 2014) - Li, Zhijian; Song, Zhen; Wu, Shubin; Xu, Keke; Jin, Di; Wang, Haijing; Liu, Ping
Abstract Purpose: To report visual outcomes and barriers to uptake of cataract surgery among subjects of all ages in Mingshui County, Heilongjiang Province, China. Methods: Cluster sampling was used to select a cross-sectional sample of people living in the Heilongjiang Province. Each subject underwent a participant interview, presenting and best-corrected vision measurements and an ocular examination. Visual outcomes and barriers to uptake of cataract surgery were assessed among subjects undergoing cataract surgery. Individuals who needed cataract surgery were interviewed regarding barriers. Results: Of 11, 787 subjects, 10, 384 eligible participants underwent visual acuity (VA) testing and a basic eye examination (88.1% response rate). The cross-sectional sub-sample of 21 participants receiving cataract surgery had a median age of 63 years. Six eyes undergoing surgery at the county hospital with conventional intracapsular and extracapsular cataract extraction without an intraocular lens implant were aphakic, and 15 eyes (71.4%) undergoing surgery at tertiary care hospitals were pseudophakic. Seven eyes (33.3%) had corrected VA ≥ 20/60, and nine eyes (42.9%) had presenting VA ≥ 20/60. Approximately 28.6% (6/21) had poor outcomes. The principal causes of presenting blindness after cataract surgery were refractive error/uncorrected aphakia and posterior capsular opacification. Cost was the most common barrier (73.9%) to uptake of cataract surgery. Conclusions: Cataract surgical outcomes in northern China were poor. The principal barrier to uptake of cataract surgery was cost. These findings call for the establishment of cataract surgical services that are of high quality, affordable, and sensitive to high-risk groups.